Prussian blue MOF material and preparation method and application thereof

CN118373429BActive Publication Date: 2026-11-03HAINAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410439422.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-12
Publication Date
2026-11-03
Estimated Expiration
2044-04-12

AI Technical Summary

Technical Problem

Traditional tumor treatment methods have significant toxic side effects, lack specificity, and have low treatment efficiency. Existing MOF nanotherapy systems have insufficient chemical kinetics in aqueous systems, making it difficult to effectively utilize water to generate strong oxidative free radicals for tumor treatment.

Method used

Prussian blue MOF material (PB-Gd) doped with rare earth element Gd was prepared. By doping Gd ions into the Prussian blue complex, a nano-therapeutic system with high chemical kinetic activity and photothermal properties was formed. The system utilizes the Fenton reaction to generate strong oxidative free radicals for tumor treatment.

Benefits of technology

PB-Gd materials significantly enhance chemical kinetics in aqueous systems, generating more strong oxidative free radicals, thereby increasing their ability to destroy tumor cells and achieving better anti-cancer effects. Moreover, the preparation method is simple and reliable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The application belongs to the technical field of Prussian blue MOF materials, and relates to a Prussian blue MOF material doped with rare earth elements and a preparation method and application thereof. The Prussian blue MOF material is formed by doping rare earth elements Gd in a Prussian blue complex, and is named PB-Gd. The content of Gd in the material is 59.82%. The PB-Gd prepared after doping Gd has improved chemical kinetic performance in a water system, and the photo-thermal performance is also enhanced. Under the assistance of photo-thermal, the chemical kinetic performance is further strengthened. The Prussian blue MOF material doped with rare earth elements has good anti-cancer treatment effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of Prussian blue MOF materials, and relates to a Prussian blue-doped MOF material, its preparation method, and its application. Background Technology

[0002] Prussian blue (PB) is a complex that has attracted widespread attention in various scientific fields due to its unique properties. Prussian blue has a face-centered cubic structure of unit cells. Based on its structure and composition, it is known as the simplest metal-organic framework (MOF) material, but it is more stable in aqueous systems than other metal-organic framework materials.

[0003] Cancer is one of the most threatening diseases to human life and health. Traditional clinical cancer treatments include radiotherapy and chemotherapy, but these have drawbacks such as significant toxic side effects, lack of specificity leading to low treatment efficiency, and high recurrence rates. Compared with traditional treatments, MOF-based nanotherapy systems have advantages such as high specific surface area, good biocompatibility, high pH sensitivity, and low toxic side effects.

[0004] MOF (Metal-Oxide-Flavors) nanotherapy systems are typically applied in tumor treatment through three pathways: starvation therapy, chemokinetic therapy, and photodynamic therapy. Chemokinetic therapy utilizes the Fenton reaction or Fenton-like reactions. The Fenton reaction generally refers to a reaction in which H₂O₂ decomposes under the catalysis of variable-valence transition metal ions to generate highly oxidizing •OH radicals. These strong oxidizing free radicals can cause irreversible oxidative damage to important components of tumor cells. This process not only disrupts the structure and function of tumor cells but also triggers irreversible intracellular reactions, ultimately leading to apoptosis. This achieves the therapeutic effect on tumors. Water is an essential component of the human body; if more strong oxidizing free radicals can be generated using water, even better therapeutic results can be achieved. Summary of the Invention

[0005] The first objective of this invention is to provide a Prussian blue MOF material, wherein the Prussian blue MOF material is a Prussian blue complex doped with the rare earth element Gd, and is named PB-Gd.

[0006] Furthermore, in the Prussian blue MOF material, the content of metal ions Gd reaches 59.82%. After doping with metal ions Gd, the Prussian blue MOF material exhibits excellent chemical kinetic activity.

[0007] The second objective of this invention is to provide a method for preparing the Prussian blue MOF material, comprising the following steps: adding an aqueous solution of potassium ferrocyanide (K4[Fe(CN)6]) containing citric acid (FA) dropwise into an aqueous solution of FeCl3 containing GdCl3, stirring at a certain temperature, collecting the product, centrifuging; adding ultrapure water and washing repeatedly by centrifugation three times, discarding the supernatant, and drying in an oven to obtain the Gd-doped Prussian blue MOF material.

[0008] Furthermore, the stirring speed is 600-700 r / min, the stirring time is 0.5-0.6 h, and the stirring temperature is 60℃.

[0009] Furthermore, the amount of citric acid added is 0.5 mmol; the concentration of the K4[Fe(CN)6] aqueous solution is 1.0 mM; the concentration of the FeCl3 aqueous solution is 1.0 mM; and the amount of gadolinium chloride added is 0.02 mmol.

[0010] A third objective of this invention is to provide the application of the Prussian blue MOF material as a Fenton reaction catalyst.

[0011] A fourth objective of this invention is to provide the application of the Prussian blue MOF material in anticancer applications.

[0012] Beneficial technical effects of the present invention: (1) The preparation method of the Prussian blue MOF material of this invention is simple and the process is stable and reliable. It also effectively incorporates rare earth elements into PB, and the Gd content of the material has been verified to be 59.82%.

[0013] The PB-Gd doped with Gd exhibits improved chemical kinetics and photothermal properties in aqueous systems, with further enhancement of chemical kinetics under photothermal assistance. These two properties can exert a synergistic effect, leading to better anti-cancer therapeutic effects. The Prussian blue MOF material is formed by utilizing the complexation of iron ions with carboxylic acids. The addition of citric acid as a surface capping agent ensures good colloidal stability during nanoparticle formation. The Prussian blue MOF material doped with rare earth element Gd provided by this invention exhibits significantly enhanced chemical kinetic activity in aqueous systems, a substantial improvement in Fenton performance, and the generation of more strong oxidizing free radicals, thereby enhancing its ability to destroy the structure and function of tumor cells and improving anti-cancer efficacy. (See attached figures.)

[0014] Figure 1 X-ray diffraction (XRD) patterns of PB-Gd, PB, and stimulated-PB; Figure 2 Here is a scanning electron microscope image of PB; Figure 3 Scanning electron microscope image of PB-Gd; Figure 4 The graph shows the Gd ion content of PB-Gd and PB-Gd@FA after being diluted and destroyed by aqua regia. Figure 5 The temperature change curves of PB and PB-Gd under 808nm laser irradiation are shown. Figure 6 The absorbance curves of PB-Gd, PB, PB-Gd@FA and PB@FA after catalytic oxidation of TMB at the same concentration are shown in the 450nm-850nm range. Figure 7 Absorbance curves at 450 nm-850 nm after catalytic oxidation of TMB by PB-Gd solutions of different concentrations; Figure 8 Absorbance curves from 450 nm to 850 nm after catalytic oxidation of TMB in PB-Gd solutions of the same concentration at different pH values; Figure 9 The absorbance at 652 nm after PB-Gd and PB-Gd@FA catalytic oxidation of TMB is shown as a function of time. Figure 10 The absorbance curves of PB and PB-Gd solutions of the same concentration after catalytic oxidation of TMB at different temperatures (450nm-850nm) are shown. Figure 11 The absorbance curves of PB and PB-Gd solutions of the same concentration after catalytic oxidation of TMB at 450nm-850nm under photothermal assistance; Figure 12 This is a statistical graph showing cell survival rates at different concentrations of PB-Gd. Detailed Implementation

[0015] The present invention will be further illustrated below with examples, but these examples do not limit the scope of protection of the present invention. Based on the technical solution of the present invention, various modifications or variations that can be made by those skilled in the art without creative effort are still within the scope of protection of the present invention.

[0016] Example 1 40 mL of solution containing 0.5 mmol of citric acid was prepared at a concentration of 1.0 × 10⁻⁶. -3 Add MK4[Fe(CN)6] aqueous solution dropwise to 40 mL of 1.0 mM FeCl3 containing 0.02 mmol GdCl3 and stir at 60°C for 0.5–0.6 h at a stirring speed of 600–700 rpm. Collect the product and centrifuge at 10,000 rpm for 15 min. Add ultrapure water and wash three times by repeated centrifugation. Discard the supernatant and dry in an oven at 45°C. This yields Gd-doped Prussian blue MoF material, abbreviated as PB-Gd.

[0017] Comparative Example 1 40 mL of solution containing 0.5 mmol of citric acid was prepared at a concentration of 1.0 × 10⁻⁶. -3 MK4[Fe(CN)6] aqueous solution was added dropwise to a concentration of 1.0 × 10⁻⁴ mL. -3 The solution of mFeCl3 was stirred at 60°C. The product was then collected and centrifuged at 15000 rpm for 15 minutes. Ultrapure water was added, and the mixture was washed three times by repeated centrifugation. The supernatant was discarded, and the product was dried in an oven at 45°C. The solid in the centrifuge tube was removed; this was Prussian blue, abbreviated as PB.

[0018] Comparative Example 2: PB-Gd@FA was obtained by physical adsorption.

[0019] Dissolve 50 mg of PB-Gd in 10 mL of deionized water by sonication, add 50 mg of folic acid, place on a magnetic stirrer, and stir. React at room temperature for 2 h, then centrifuge at 10000 r / min for 10 min, discard the supernatant, wash with ultrapure water, repeat centrifugation and washing 3 times, discard the supernatant, dry in an oven, and remove the solid from the centrifuge tube to obtain folic acid-modified Prussian blue doped with Gd, abbreviated as PB-Gd@FA.

[0020] Comparative Example 3 Dissolve 50 mg of PB-Gd in 10 mL of deionized water by sonication, add 50 mg of folic acid, place on a magnetic stirrer, and stir. React at room temperature for 2 hours, then centrifuge at 10000 rpm for 10 minutes. Discard the supernatant, wash with ultrapure water, and repeat centrifugation and washing three times. Discard the supernatant, place in an oven to dry, and remove the crystalline powder from the centrifuge tube to obtain folic acid-modified Prussian blue, abbreviated as PB@FA.

[0021] Material characterization: (1) X-ray diffraction analysis Experimental procedure: X-ray diffraction measurements were performed on PB-Gd and PB obtained in Example 1 and Comparative Example 1 using an X-ray diffractometer. The obtained X-ray diffraction patterns are as follows: Figure 1 As shown.

[0022] Experimental results: Depend on Figure 1 It can be seen that after PB is doped with the rare earth element Gd, its crystal structure is not affected and it still maintains a complete crystal structure.

[0023] (2) Scanning electron microscopy experiment Experimental procedure: Scanning electron microscopy was used to perform scanning electron microscopy on PB-Gd and PB obtained in Example 1 and Comparative Example 1, respectively. The obtained scanning electron microscopy images are shown below. Figure 2 and Figure 3 As shown.

[0024] Experimental results: Depend on Figure 2 and Figure 3 It can be seen that PB-Gd exhibits a regular tetrahedral morphology with a size of approximately 100 nm. Its morphology and size are not significantly different from PB.

[0025] (3) Determination of Gd content in PB-Gd and PB-Gd@FA materials.

[0026] Experimental Procedure: A series of Gd solutions with known concentration gradients were prepared using a standard Gd solution to construct a standard curve. 2 mg of PB-Gd obtained in Example 1 was weighed and dissolved in 200 μl of aqua regia. After complete dissolution, 1.8 ml of 1% nitric acid solution was added, and dissolution continued. 0.5 ml of each solution was transferred to two centrifuge tubes and diluted tenfold. This constitutes two parallel groups. The above steps were repeated to perform parallel experiments. The test solution of PB-Gd@FA obtained in Comparative Example 2 was prepared using the same method, and the above process was repeated.

[0027] The formula for calculating Gd content is as follows: Where m is the mass of Gd loaded in the material, and M is the total mass of the products prepared in the examples and comparative examples. The experimental results are as follows: Figure 4 As shown.

[0028] Depend on Figure 4 It can be seen that the Gd content of PB-Gd is 59.82%; the Gd content of PB-Gd@FA is 17.46%.

[0029] (4) Measurement of photothermal properties Experimental procedure: PB-Gd obtained in Example 1 and PB obtained in Comparative Example 1 were prepared into a 1 mg / mL aqueous solution. The solution was then analyzed using an 808 nm wavelength laser with an energy density of 2.04 W / mL. Irradiation was performed for 10 minutes each time, and the temperature change of the solution over time was recorded using a thermal imager. The experimental results are as follows: Figure 5 As shown.

[0030] Depend on Figure 5 It can be seen that, under the same time and energy density, the temperature rise of PB-Gd is higher than that of PB, thus indicating that the photothermal performance of PB is enhanced after Gd doping.

[0031] (5) Determination of chemical kinetic activity Experimental steps: Experiment 1: PB-Gd obtained in Example 1, PB obtained in Comparative Example 1, PB-Gd@FA obtained in Comparative Example 2, and PB@FA obtained in Comparative Example 3 were dissolved in PBS solution at pH=5 to prepare solutions with a concentration of 50 μg / mL. Then, 100 μL of the sample solution, 100 μL of ultrapure water, 50 μL of TMB-A solution, and 50 μL of TMB-B solution (TMB-A solution was prepared by dissolving anhydrous sodium acetate, glacial acetic acid, and urea peroxide in ultrapure water; TMB-B solution was an aqueous solution prepared by dissolving TMB in acetone with anhydrous citric acid and EDTA-2Na) were sequentially added to 96-well plates. The plates were incubated in the dark at 37°C for 15 min before being measured using a microplate reader. The main component of TMB-A solution is hydrogen peroxide, and the main component of TMB-B solution is 3,3',5,5'-tetramethylTMB. The experimental results are as follows: Figure 6 As shown.

[0032] according to Figure 6 It can be seen that the chemical kinetic activity of PB was improved after Gd doping, while the chemical kinetic activity of modified folic acid was reduced.

[0033] Experiment 2: Different masses of PB-Gd prepared in Example 1 were dissolved in PBS solution at pH=5 to obtain solutions with concentrations of 5 μg / mL, 10 μg / mL, 20 μg / mL, 30 μg / mL, 40 μg / mL, and 50 μg / mL. Then, 100 μL of the sample solution, 100 μL of ultrapure water, 50 μL of TMB-A solution, and 50 μL of TMB-B solution were added sequentially to 96-well plates. The plates were incubated in the dark at 37°C for 15 min before being analyzed using a microplate reader. The experimental results are as follows: Figure 7 As shown.

[0034] according to Figure 7 It can be seen that, at the same reaction temperature and within the same reaction time, the chemical kinetic activity of PB-Gd obtained in Example 1 increases with increasing concentration.

[0035] Experiment 3: PB-Gd prepared in the previous experiment was dissolved in PBS solutions at pH 3, pH 4, pH 6, and pH 7.4 to prepare solutions with a concentration of 50 μg / mL. Then, 100 μL of sample solution, 100 μL of ultrapure water, 50 μL of TMB-A solution, and 50 μL of TMB-B solution were added sequentially to each well of a 96-well plate. The plates were incubated in the dark at 37°C for 15 min before being analyzed using a microplate reader. The experimental results are as follows: Figure 8 As shown.

[0036] according to Figure 8It can be seen that, under the same reaction temperature, the same reaction time, and the same concentration, the chemical kinetic activity of PB-Gd obtained in Example 1 decreases with increasing pH value.

[0037] Experiment 4: PB-Gd obtained in Example 1, PB obtained in Comparative Example 1, and PB-Gd@FA obtained in Comparative Example 2 were dissolved in PBS solution at pH=5 to prepare solutions with a concentration of 50 μg / mL. Then, 100 μL of the sample solution, 100 μL of ultrapure water, 50 μL of TMB A solution, and 50 μL of TMB B solution were sequentially added to a 96-well plate. Measurements were taken once per minute at room temperature. The experimental results are as follows: Figure 9 As shown.

[0038] according to Figure 9 It can be seen that, within 20 minutes, the chemical kinetic activity of PB-Gd obtained in Example 1 and PB-Gd@FA obtained in Comparative Example 2 increased with time.

[0039] Experiment 5: PB-Gd obtained in Example 1 and PB obtained in Comparative Example 1 were dissolved in PBS solution at pH=5 to obtain a solution with a concentration of 200 μg / mL. Then, 50 μL of the sample solution, 50 μL of ultrapure water, 50 μL of TMB-A solution, and 50 μL of TMB-B solution were added sequentially to a 96-well plate. The 96-well plates were then placed in ovens at 37℃, 45℃, and 50℃ for 10 min, respectively, and the results were measured using a microplate reader. The experimental results are as follows: Figure 10 As shown.

[0040] Depend on Figure 10 It can be seen that PB-Gd and PB at the same concentration have different chemical kinetic activities at different reaction temperatures within the same reaction time; the higher the temperature, the stronger the chemical kinetic activity.

[0041] (6) Determination of the synergistic effect of photothermal and chemical kinetic properties Experimental Procedure: PB-Gd prepared in Example 1 and PB prepared in the comparative example were each prepared into 200 μg / mL solutions. These solutions were then irradiated with an 808 nm laser at an energy density of 2.04 W / mL until the temperature reached 45°C as indicated by a thermal imager. 50 μL of the sample solution, 50 μL of ultrapure water, 50 μL of LMB-A solution, and 50 μL of LMB-B solution were then added sequentially to 96-well plates. After reacting for 10 min, the results were measured using a microplate reader. The experimental results are as follows: Figure 11 As shown.

[0042] Depend on Figure 11 It can be seen that, with the assistance of photothermal energy, the PB-Gd obtained in Example 1 with the same concentration, the same material, and the same reaction time has improved chemical kinetic activity compared to the PB obtained in Comparative Example 1.

[0043] (7) Determination of anti-cancer ability Experimental Procedure: 4T1 mouse breast cancer cells in logarithmic growth phase and good growth status were collected and digested, removing the original culture medium. The cells were washed twice with 2 mL of PBS solution, followed by 1 mL of trypsin and incubation for 3 min. After digestion, 4 mL of complete culture medium (containing 10% fetal bovine serum and 1% penicillin antibiotics) was added to terminate the digestion. The cells were centrifuged at 1250 r / min for 5 min, the supernatant was removed, and 9 mL of complete culture medium was added and mixed thoroughly. Cell counting was performed, and a cell suspension was prepared according to experimental requirements, with 1 × 10⁶ cells per well. 4 Cells were seeded into 96-well plates and incubated for 24 hours. After cell attachment, the original culture medium was removed, and 200 μL of 1640 medium solution and different concentrations of PB-Gd experimental solution were added to each well. After drug addition, the plates were incubated for another 24 hours. After incubation, the drug-containing medium was aspirated, and 100 μL of 10% CCK-8 reagent was added to each well. The plates were then incubated at 37 °C for another 2 hours. Finally, the absorbance of each well was measured at 450 nm using a microplate reader, and the data were recorded. The corresponding cell viability was calculated using the following formula: Experimental results are as follows Figure 12 As shown.

[0044] Depend on Figure 12 It can be seen that PB-Gd has a certain killing ability on 4T1 cells, and this ability tends to increase with the increase of PB-Gd concentration.

Claims

1. A Prussian blue MOF material, characterized in that: The Prussian blue MOF material is formed by doping rare earth element Gd into a Prussian blue complex and is named PB-Gd. The preparation method of the Prussian blue MOF material is as follows: potassium ferrocyanide aqueous solution containing citric acid is added dropwise to FeCl3 aqueous solution containing GdCl3, stirred at a certain temperature, the product is collected and centrifuged; ultrapure water is added and the mixture is repeatedly centrifuged and washed three times, the supernatant is discarded, and the mixture is dried in an oven to obtain Prussian blue MOF material doped with Gd. The stirring speed is 600-700 r / min, the stirring time is 0.5-0.6 h, and the stirring temperature is 60℃. The amount of citric acid added is 0.5 mmol; the concentration of the K4[Fe(CN)6] aqueous solution is 1.0 mM; the concentration of the FeCl3 aqueous solution is 1.0 mM; and the amount of gadolinium chloride added is 0.02 mmol. In the Prussian blue MOF material, the content of metal ion Gd reaches 59.82%. After doping with metal ion Gd, the Prussian blue MOF material exhibits excellent chemical kinetic activity.

2. A method for preparing the Prussian blue MOF material as described in claim 1, characterized in that: The process includes the following steps: adding potassium ferrocyanide aqueous solution containing citric acid dropwise into FeCl3 aqueous solution containing GdCl3, stirring at a certain temperature, collecting the product, centrifuging; adding ultrapure water and washing repeatedly by centrifugation three times, discarding the supernatant, and drying in an oven to obtain Prussian blue MOF material doped with Gd. The stirring speed is 600-700 r / min, the stirring time is 0.5-0.6 h, and the stirring temperature is 60℃. The amount of citric acid added is 0.5 mmol; the concentration of the K4[Fe(CN)6] aqueous solution is 1.0 mM; the concentration of the FeCl3 aqueous solution is 1.0 mM; and the amount of gadolinium chloride added is 0.02 mmol.

3. The application of the Prussian blue MOF material as described in claim 1 or the Prussian blue MOF material prepared by the preparation method described in claim 2 as a Fenton reaction catalyst.

4. The application of a Prussian blue MOF material as described in claim 1 or a Prussian blue MOF material prepared by the preparation method described in claim 2 in anticancer applications.

Citation Information

Patent Citations

  • Magnetic resonance imaging contrast agent for gadolinium-doped Prussian blue material

    CN108721650A

  • Preparation method and application of bimetallic Prussian blue analogue catalyst

    CN113908878A